Strategi Pemasaran Radio Kardopa dalam Meningkatkan Minat Pendengar Muda di Kota Medan, Provinsi Sumatera Utara - Sri Rahmadani; Bunayyati Hakimah S. Meliala (Cakrawala: Jurnal Kajian Manajemen Pendidikan Islam dan studi sosial, 2023)
Technological advances have recently become the concern of all human beings, especially with this broadcasting institution, Radio Kardopa 99.4 FM. One of the things that must be able to compete with the development of an era that is increasingly rapid in its growth is technology. Initially, this radio only distributed information in a traditional way, such as through accessing only FM transmitters. Which in this day and age is considered old-fashioned and less effective because not everyone is interested in listening to radio on a frequency transmitter. So a live streaming radio and social media platform was created to convey information. On this occasion, the author uses a digitalized marketing strategy using access to social media as an information distribution strategy. So wherever they are they will always be able to listen to their favorite radio. To increase its audience, the broadcaster has evaluated the strategy used. Where this broadcasting institution, namely Kardopa Radio itself, already has a Tiktok account which aims to increase listeners, namely young people or millennials and gen-z. This is done because Kardopa Radio knows very well that information does not only belong to certain groups, but belongs to all groups, including the young people. It can be seen from the follower insight data that many follow the @radiokardopa.kdigi account, the age of 25-34 is 39.0% and the age of 18-24 is 32.0%. It is clear that the target to be achieved has been accomplished during the author's internship at this place. In this study the authors used a qualitative method with a descriptive case study approach, this aims to increase the interest of young listeners and is designed through an effective approach.